Managing classrooms to facilitate learning - Bauer, Anne M.; Sapona, Regina H. (Englewood Cliffs, NJ : Prentice-Hall, 1991)
This work aims to help pre-service and in-service teachers increase their skills in managing children with challenging behaviours in the classroom, by offering details of a classroom management framework and pro-active problem-solving techniques. Practice interaction scripts are included.
Includes bibliographical references and index.
Keywords: Classroom management -- United States